EXPLORING GEOTHERMAL ZONES IN NORTHERN NIGERIA USING LAND SURFACE TEMPERATURE DATA FROM REMOTE SENSING - Ahile, Joseph Aza; Meludu, Osita Chukwudi; Oniku, Adetola Sunday (FUDMA JOURNAL OF SCIENCES, 2025)
Nigeria is still unable to meet even the most basic of its energy needs, this lack of power is most evident in houses located in the North-Central and North-East areas. This paper focused on evaluating geothermal potential through remote sensing techniques in parts of Northern Nigeria. Four digital elevation model (DEM) scenes, three Landsat-9(OLI-2/TIR-2) with minimum zero or minimum cloud cover (<6%), and Terra Moderate Resolution Imaging Spectroradiometer satellite images for the research region were processed using ArcMap 10.7.1, Google Earth Pro, and QGIS 3.36.3. The linear correlation analysis performed between Landsat LST and MODIS LST images showed a high correlation coefficient (R² = 0.907). Anomalously high lineament density correlates with high land surface temperature, dominantly in the basement complex of the study area; it’s possible that the fracturing will increase the permeability, enabling warm or hot springs to rise to the surface. Fault lines that permit the movement of hot/warm water to the Earth’s surface can be linked to active geothermal zones. The stream/rivers in or around the targeted high LST are probably thermal springs, as they were overlaid on the LST, and high-temperature spots(>280) were identified. The regions around Jibam, Langtang, Aikri, Adikpo, Shemdam, and Ashinge prove to be areas where warm or hot springs can be located.